'The first of the small nations': the significance of central European small states in Irish nationalist political rhetoric, 1918–22. Issue 165 (May 2020) - Zách, Lili
Abstract: Offering new insights into Irish links with the wider world, this article explores and contextualises Irish nationalist perceptions of and links with central European small states in the immediate aftermath of the First World War. The belief that any small nation like Ireland, oppressed by a dominant neighbour, had the right to self-determination was of key importance in nationalist political rhetoric during the revolutionary years. Given the similarity of circumstances among newly independent small states, Irish commentators were aware of the struggles Ireland shared with the successors of the Austro-Hungarian Empire. Personal encounters on the continent, as well as news regarding small nations in central Europe, shaped Irish opinions of the region. Certainly, the images presented by Irish commentators reflected their own political agendas and were therefore often deliberately idealistic. Nonetheless, they served a specific purpose as they were meant to further Ireland's interest on the international stage. Looking beyond Ireland for lessons and examples to follow became a frequent part of Irish nationalist political rhetoric. By directing scholarly attention to a hitherto less explored aspect of Irish historiography, this article aims to highlight the complexity of Ireland's connection with the continent within the framework of small nations, from a transnational perspective.